2018
DOI: 10.1128/aac.00885-18
|View full text |Cite|
|
Sign up to set email alerts
|

Population Pharmacokinetics and Cerebrospinal Fluid Penetration of Fluconazole in Adults with Cryptococcal Meningitis

Abstract: Robust population pharmacokinetic (PK) data for fluconazole are scarce. The variability of fluconazole penetration into the central nervous system (CNS) is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…First, the fluconazole concentrations were obtained from 1 clinical study that included 92 HIV-infected Ugandans that used the linear kinetic model for predicting the exposure from different doses. Our steady plasma concentrations were within 10%–20% of observations in US, Vietnamese, and other Ugandan patients [12, 17]. Second, the timing of the fluconazole level draw was variable, which either could under- or overestimate the AUC calculation, but multiple samples were averaged.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…First, the fluconazole concentrations were obtained from 1 clinical study that included 92 HIV-infected Ugandans that used the linear kinetic model for predicting the exposure from different doses. Our steady plasma concentrations were within 10%–20% of observations in US, Vietnamese, and other Ugandan patients [12, 17]. Second, the timing of the fluconazole level draw was variable, which either could under- or overestimate the AUC calculation, but multiple samples were averaged.…”
Section: Discussionsupporting
confidence: 51%
“…Finally, the exact target AUC above MIC ratio for consolidation therapy is unknown, and we have made an arbitrary approximation. Human data and excellent modeling has been conducted for fluconazole induction therapy [12], yet consolidation therapy recommendations has been derived mostly from expert opinion. Based on historical experience, the doses of fluconazole used during consolidation have been less than that used for induction fluconazole monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The CSF‐to‐plasma fluconazole concentration ratio has been shown to exceed 0.8 in adults . Furthermore, a recently published PopPK study in adults with cryptococcal meningitis found the mean fluconazole area under the concentration‐time curve of CSF to plasma to be 0.89 . Although this ratio was previously unknown for the pediatric population, in this study the range of simulated plasma and simulated CSF concentrations were approximately the same (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adequate concentrations do not predict successful outcomes of FCZ alone in the treatment of CNS cryptococcal infections 18 . Although FCZ monotherapy even at higher dose is not recommended for cryptococcal meningitis therapy, in many regions of the world, FCZ is the only available drug for induction therapy for cryptococcal meningitis 91 . These is a need for improved provision of available combination treatments and development of more effective drugs 91 …”
Section: Triazolesmentioning
confidence: 99%